A NEW STABILITY-INDICATING RP-HPLC METHOD FOR DETERMINATION OF CURCUMIN: AN APPLICATION TO NANOPARTICULATE FORMULATION - Panigrahi, Suchitra; Hirlekar, Rajashree (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The present study was aimed to develop a rapid, accurate, linear, sensitive and stability-indicating high performance liquid chromatographic method for determination of curcumin and to implement the developed method for the estimation of curcumin in the nanoparticulate formulation. Methods: Method development was performed using various solvent, buffer-solvent ratios, at different flow rates for better resolution and to decrease the run time. The developed method was validated in accordance with the international conference on harmonization (ICH) guidelines. The developed method was implemented to estimate the amount of curcumin in the curcumin-nanoparticulate formulation. Results: The optimum chromatographic conditions with adequate resolution for curcumin (16.10 min) was achieved when the separation was carried using C18 column at ambient temperature with an isocratic elution mode of mobile phase composed of a degassed mixture of phosphate buffer pH 3 and acetonitrile (50:50 v/v) at 1.0 ml/min flow rate with a total run time of 20 min. The developed method was validated for system suitability, accuracy, precision, limit of detection (LOD), limit of quantitation (LOQ), linearity and range. The LOD and LOQ were found to be 0.018 and 0.056 Î¼g/ml respectively, which indicates that the method was sensitive, and can detect and quantify at lower levels of curcumin. Linearity range was from 5-15 Î¼g/ml for curcumin with regression coefficient 0.997 indicates that at this concentration range curcumin was highly linear. Percent assay of curcumin was found to be 98.7% and curcumin recovered was found to be 0.78 mg which are estimated by using the developed method. Conclusion: The developed analytical method is simple, precise, and reproducible and thus can be used for stability-indicating analysis of curcumin in pharmaceutical formulations.